2009
DOI: 10.1103/physrevb.79.092413
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous spin waves and the commensurate-incommensurate magnetic phase transition inLiNiPO4

Abstract: Detailed spin-wave spectra of magneto-electric LiNiPO4 have been measured by neutron scattering at low temperatures in the commensurate (C) antiferromagnetic (AF) phase with TN = 20.8 K. An anomalous low-energy mode is observed at the modulation vector of the incommensurate (IC) AF phase appearing above TN . A linear spin-wave model based on Heisenberg exchange couplings and single ion anisotropies accounts for all the observed spin-wave dispersions and intensities. Along the b axis an unusually strong next-ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 16 publications
10
47
0
1
Order By: Relevance
“…9, an investigation of the spin excitations revealed that there are three relatively strong exchange couplings in the bc plane (J bc ∼ 0.5 meV) and two much weaker out-of-plane couplings (J a ∼ 0.05 meV) as in the other lithium orthophosphates. 10,11 As expected, a very weak single ion anisotropy (D ≈ 0.008 meV) was found, compared to the strongest in-plane nearest-neighbor exchange interactions. Thus, LiMnPO 4 is a pseudo-2D Heisenberg system and has been found to exhibit a spin-flop [12][13][14][15] transition, which is a nearly 90…”
Section: Introductionsupporting
confidence: 76%
“…9, an investigation of the spin excitations revealed that there are three relatively strong exchange couplings in the bc plane (J bc ∼ 0.5 meV) and two much weaker out-of-plane couplings (J a ∼ 0.05 meV) as in the other lithium orthophosphates. 10,11 As expected, a very weak single ion anisotropy (D ≈ 0.008 meV) was found, compared to the strongest in-plane nearest-neighbor exchange interactions. Thus, LiMnPO 4 is a pseudo-2D Heisenberg system and has been found to exhibit a spin-flop [12][13][14][15] transition, which is a nearly 90…”
Section: Introductionsupporting
confidence: 76%
“…An unusual minimum in the spinwave dispersions in the AFM commensurate ground state was observed at the modulation vector of the IC phase and was explained as the precursor of the C-IC phase transition that originates from a trade off between competing Heisenberg interactions of nearest-and next-nearest-neighboring Ni 2+ ions and an extra lock-in energy at lower temperatures originating from the strong single-ion anisotropies found in the system. 18 We have recently reported the spin dynamics and magnetic properties of the isostructural LiFePO 4 , LiCoPO 4 , and LiMnPO 4 systems and found no evidence for an IC phase and no anomalous spin-wave dispersions. [19][20][21] In the present study we have substituted Fe for Ni to form LiNi 1−x Fe x PO 4 single crystals with up to x = 0.2 to compare with the magnetic behavior of the parent material and shed further light on the IC phase in LiNiPO 4 .…”
Section: -0121/2009/79͑17͒/174435͑7͒mentioning
confidence: 99%
“…6. The small canting of the Ni 2+ spins has a negligible influence on the spin-wave model, 18 so for simplicity we have assumed a ground state with spins pointing strictly along the c axis. The in-plane NN coupling ͑J 1 ͒ is mediated by an oxygen through a Ni 2+ -O-Ni 2+ bond.…”
Section: Linear Spin-wave Theorymentioning
confidence: 99%
See 2 more Smart Citations